The cyclin D1 proto-oncogene is sequestered in the cytoplasm of mammalian cancer cell lines - Coombes R Charles; Lam Eric; Pomeranz Karen M; Stavropoulou Alexandra V; Gamble Simon C; Alao John P; Vigushin David M (Molecular Cancer, 2006)
Abstract Background The cyclin D1 proto-oncogene is an important regulator of G1 to S-phase transition and an important cofactor for several transcription factors in numerous cell types. Studies on neonatal cardiomyocytes and postmitotic neurons indicate that the activity of cyclin D1 may be regulated through its cytoplasmic sequestration. We have demonstrated previously, that TSA induces the ubiquitin-dependent degradation of cyclin D1 in MCF-7 breast cancer cells. Additional studies were initiated in order to further investigate the effect of TSA on cyclin D1 regulation using sub-cellular fractionation techniques. Results Our studies revealed cyclin D1 to be localized predominantly within the cytoplasmic fraction of all cell lines tested. These observations were confirmed by confocal microscopy. GSK3β was found to be localized within both the nucleus and cytoplasm throughout the cell cycle. Inhibition of GSK3β or CRM1-dependent nuclear export resulted in only modest nuclear accumulation, suggesting that the cytoplasmic localization of cyclin D1 results from the inhibition of its nuclear import. Conclusion We have shown by several different experimental approaches, that cyclin D1 is in fact a predominantly cytoplasmic protein in mammalian cancer cell lines. Recent studies have shown that the cytoplasmic sequestration of cyclin D1 prevents apoptosis in neuronal cells. Our results suggest that cytoplasmic sequestration may additionally serve to regulate cyclin D1 activity in mammalian cancer cells.